Stellar Atmospheric Parameters of ∼11,000 RR Lyrae Stars from LAMOST Spectra - Wang, Jiangtao; Shi, Jianrong; Fu, Jianning; Zong, Weikai; Li, Chunqian (The Astrophysical journal. Supplement series, 2024)
Accurate determination of the stellar atmospheric parameters of RR Lyrae stars (RRLs) requires short individual exposures of the spectra to mitigate pulsation effects. We present improved template-matching methods to determine the stellar atmospheric parameters of RRLs from single-epoch spectra of the Large Sky Area Multi-Object Fiber Spectroscopic Telescope, also known as the Guoshoujing Telescope (LAMOST). We determine the radial velocities and stellar atmospheric parameters (effective temperature T eff , surface gravity log g , and metallicity [M/H]) of 10,486 and 1027 RRLs from 42,729 LAMOST low-resolution spectra (LRS) and 7064 LAMOST medium-resolution spectra (MRS), respectively. Our results are in good agreement with the parameters of other databases, where the external uncertainties of T eff , log g , and [M/H] for LRS/MRS are estimated to be 207/142 K, 0.21/0.16 dex, and 0.24/0.18 dex, respectively. We conclude with the variation characteristics of the radial velocities (RV) and stellar atmospheric parameters for RRLs during the pulsation phase. There is a significant difference of 28 ± 21 km s −1 between the peak-to-peak amplitude ( A ptp ) of RV from the H α line (RV H α ) and from metal lines (RV metal ) for RRab, whereas it is only 4 ± 17 km s −1 for RRc. The A ptp of T eff is 930 ± 456 and 409 ± 375 K for RRab and RRc, respectively. The log g of RRab shows a mild variation of approximately 0.22 ± 0.42 dex near the phase of φ = 0.9, while that of RRc almost remains constant. The [M/H] of RRab and RRc show a minor variation of about 0.25 ± 0.50 and 0.28 ± 0.55 dex, respectively, near the phase of φ = 0.9. We expect that the determined stellar atmospheric parameters would shed new light on the study of stellar evolution and pulsation, the structure of the Milky Way, as well as other research fields.